Regarding “Effectiveness and Persistence of Anti-TNFα Treatment in Patients with Rheumatoid Arthritis – A 7 Years Real-World Cohort Study” [Response to Letter] - Santos-Moreno P (Biologics: Targets & Therapy)
Pedro Santos-Moreno Rheumatology Department, Biomab IPS, Bogotá, ColombiaCorrespondence: Pedro Santos-Moreno, Email pedrosantosmoreno@hotmail.com